Design and water-saving capacity of planting roof with compound irrigation and stab-resistant function - Fan, Zhenggen; Liu, Ji; Fan, Yuqi; Pan, Jiasen (Journal of Environmental Engineering and Landscape Management, 2024)
With the continuous development of urban construction, the contradiction between human settlement and the natural environment is becoming increasingly prominent. Increasing the green area and improving the local environment and microclimate through roof planting can effectively alleviate this contradiction. On the basis of the research on the current situation and challenging problems of planting roofs, a comprehensive study of construction, stab-resistance, waterproofing, irrigation and plant landscape is combined with a designed roof case. Research results show that the planting roof is simple in construction, has high resistance to plant root thorns, can take into account the function and aesthetics of plant landscape design, and saves irrigation water by more than 60%, which will help the popularization and promotion of urban planting roofs.